MEMBEDAH REALITAS KOMUNIKASI LINTAS AGAMA DI MEDIA MASSA (Critical Discourse Analisys terhadap Kompas tahun 2015) - Umi Halwati (IAIN Purwokerto, 2016)
Abstract: The consequence of a plural society is social conflict. An attitude that can stimulate conflict is exclusivism, primordial ethnicity, race and religion. The existence of an interfaith communication cannot be separated from the mass media. The mass media is a tool or an effective mediator in the publication of ideology in the stage win public support. Therefore, it is necessary to study scientifically how the media constructs a discourse of reality. This study is qualitative research using critical discourse analysis approach. The results of this study describe how the Kompas newspaper construct a discourse, both in terms of thematic, schematic, semantic, syntactic, rhetorical, and in terms of the social aspect of the analysis. Keyword: inter-religious communication, media.